E-business Startup Model using Canvas Business Model (case study: SiJasPro) - Muhaimin Hasanudin; Dedy Prasetya Kristiadi; Budi haryanto (IJISTECH (International Journal of Information System and Technology), 2021)
With the rapid development of information technology today, more and more businesses are using the internet as a medium to disseminate information and choose the right business model in order to survive and develop. This study aims to determine the business model of a startup in the Project Services Information System (sijaspro) by conducting analysis and evaluation to determine the strengths, weaknesses, opportunities, and threats so that they can design a business model. The research method used is a qualitative method. This study uses the theory of the business model canvas and SWOT analysis. The results show that the company's business model requires several additional factors in each element of the e-business model in order to grow and develop better by providing building project features and services and applications to users